Mallet Toes, Hammertoes, Neuromas, and Metatarsophalangeal Joint Instability: 40 Years of Development in Forefoot Surgery - Dang, Debbie Y. (Indian J Orthop, 2020)
BACKGROUND: Today’s foot and ankle surgeon has an enhanced understanding of forefoot pathology and treatment options compared to surgeons who practiced in previous decades. This paper summarizes developments in forefoot surgery in the past 40 years, specifically in treatments for mallet toe, hammertoe, neuroma, and metatarsophalangeal joint instability. MATERIALS AND METHODS: A review of the literature was conducted using the PubMed search engine, with key terms including, “mallet toe,” “hammertoe,” “neuroma,” “metatarsophalangeal joint instability,” “plantar plate,” and “forefoot surgery.” Chapters in major orthopaedic textbooks covering these topics were also reviewed. We then chronicled the history of the diagnosis and treatment of these pathologies, with a focus on the past 40 years. CONCLUSIONS: There have been major advances in understanding and treating forefoot pathologies in the past four decades; however, there remain areas for improvement both in the diagnosis and treatment of these problems. LEVEL OF EVIDENCE: Level V, meta-synthesis.